2019
DOI: 10.1155/2019/3784529
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trend of Neonatal Septicemia and Antibiotic Susceptibility Pattern of Isolates in Nepal

Abstract: Background. Neonatal septicemia is one of the most common leading reasons for neonatal morbidity and mortality in developing countries. Frequent monitoring on pathogens with recent updates and their antimicrobial sensitivity pattern is mandatory for the better treatment. The aim of the study was to determine the bacteriological profile of neonatal septicemia and their antibiotic susceptibility pattern. Methods. This was a cross-sectional study conducted in Outpatient Department (OPD), Neonatal Intensive Care U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 27 publications
(25 reference statements)
12
28
2
Order By: Relevance
“…The present study showed EONS to be more common than LONS which accords to studies done by Thapa, et al Pokhrel, et al and Patel, et al 4 , 11 , 16 whereas contrasts to the studies done by Yadav, et al and Shehab, et al where LONS was more common. 15 , 19 This may be because, most of the neonates with EONS in the present study were outborn (76.5%) and horizontal transmission of bacteria might have occurred from the delivery rooms, NICU rooms, during transportation or vertical transmission from mother's genital tract colonized with the pathogens.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study showed EONS to be more common than LONS which accords to studies done by Thapa, et al Pokhrel, et al and Patel, et al 4 , 11 , 16 whereas contrasts to the studies done by Yadav, et al and Shehab, et al where LONS was more common. 15 , 19 This may be because, most of the neonates with EONS in the present study were outborn (76.5%) and horizontal transmission of bacteria might have occurred from the delivery rooms, NICU rooms, during transportation or vertical transmission from mother's genital tract colonized with the pathogens.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to another study conducted by Thapa et al (10.8%). 11 Lower positivity rate (6.2%) was elicited in a study conducted in India, 12 whereas higher positivity rate was elicited in studies done in Kanti Children's hospital (16.9%), Patan hospital (20.7%), India (46.0%) and Egypt (42.8%). 13 16 The variation may be due to the culture techniques, administration of antibiotics before obtaining culture specimen and study designs.…”
Section: Discussionmentioning
confidence: 89%
“…In a developing country such as Nepal and Pakistan, where there is excessive use of antibiotics, there is an increased risk of antibiotic resistance to the microbes causing va-rious community and hospital-acquired infection. The high prevalence of antimicrobial resistance was observed against certain common bacterial clinical isolates (Staphylococcus aureus, E. coli) for the commonly used antibiotics like amoxicillin, cotrimoxazole, fluoroquinolones and third-generation cephalosporins in Nepal and Pakistan [8,9]. There must be proper follow of standard guidelines, and the prescriber should have proper knowledge of the biology of microbes.…”
Section: Introductionmentioning
confidence: 99%
“…and Citrobacter spp. These bacteria are mostly acquired from the hospital environments, health professionals, and medical devices [33,34]. Moreover, as majority of our study participants (84.1%) had early onset neonatal sepsis, the bacterial etiologies identified in our study somehow deviate from expectations [1,3,4].…”
Section: Discussionmentioning
confidence: 67%